1999
DOI: 10.1034/j.1399-3003.1999.14a04.x
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast reduces airway eosinophilic inflammation in asthma: a randomized, controlled trial

Abstract: Leukotrienes are pro-inflammatory mediators which may contribute to tissue, sputum, and blood eosinophilia seen in allergic and inflammatory diseases, including asthma. Montelukast is a cysteinyl leukotriene 1 (CysLT 1 ) receptor antagonist which improves asthma control; the aim of this study was to investigate its effect on induced sputum eosinophils.Montelukast 10 mg (n=19) or placebo (n=21) were administered orally once in the evening for 4 weeks to 40 chronic adult asthmatic patients, aged 19±64 yrs, in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
168
3
10

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(194 citation statements)
references
References 31 publications
12
168
3
10
Order By: Relevance
“…Intratracheal administration of LTD 4 promotes eosinophil sequestration into the airways (5,6). CysLTR antagonists reduce eosinophilic inflammation of the airways in asthma (7,8). The role of CysLTs in eosinophilic inflammation has been studied in several in vitro experiments.…”
mentioning
confidence: 99%
“…Intratracheal administration of LTD 4 promotes eosinophil sequestration into the airways (5,6). CysLTR antagonists reduce eosinophilic inflammation of the airways in asthma (7,8). The role of CysLTs in eosinophilic inflammation has been studied in several in vitro experiments.…”
mentioning
confidence: 99%
“…In a double blind, randomized, controlled, parallel group study over 4 weeks, montelukast improved clinical outcomes and reduced the sputum eosinophil count; during placebo treatment sputum eosinophils increased [72].…”
Section: Inflammation and Treatmentmentioning
confidence: 99%
“…Many investigators have reported an association between cPLA 2 metabolites and Th2 response in asthmatic reactions [33][34][35][36]. Importantly, LTs play a key role in dendritic cell influx into airways in asthma [37][38][39] which, in turn, results in inhibition of recruitment of T cells and eosinophils into asthmatic airways and late AHR. Regarding neutrophil infiltration, we reported previously that airway neutrophilia in the asthmatic lungs is mediated by LTB4 rather than CXC chemokines such as keratinocyte-derived chemokine and macrophage inflammatory protein (MIP)-2 [20], which are principally chemotactic for neutrophils.…”
Section: Discussionmentioning
confidence: 99%